Vasopressin Is Not Associated With Severe Kidney Injury in Liver Transplantation: A Propensity Score-adjusted Analysis - Edoardo Antonucci, MD; Michael P. Bokoch, MD, PhD; Dieter Adelmann, MD, PhD; Kerstin Kolodzie, MD, PhD, MAS; Garrett R. Roll, MD; Elizabeth Sun, MD; Matthieu Legrand, MD, PhD; Rishi Kothari, MD (Transplantation Direct)
Background. Hypotension during liver transplantation often requires vasopressor therapy. Acute kidney injury is a common complication after liver transplantation. Vasopressin acts as a portal flow modulator, may increase the glomerular filtration rate, and reduce the dose of catecholamines required. We hypothesized that intraoperative vasopressin use could be associated with reduced postoperative acute kidney injury. Methods. This single-center retrospective cohort study included 1120 adult liver transplant recipients between June 2012 and November 2022. We assessed the association between intraoperative vasopressin use and postoperative severe acute kidney injury by using a propensity score-adjusted multivariable regression model. Results. The incidence of severe postoperative acute kidney injury was 29.2%. The median age was 60 y, 64.9% of patients were males. Vasopressin was used in 34.0% of the cases. Patients receiving vasopressin had a higher Model for End-Stage Liver Disease-sodium score (24 versus 16, P < 0.001). The median [interquartile range] dose of catecholamine vasopressors was significantly higher in patients who received vasopressin (0.08 [0.05–0.12] versus 0.03 [0.01–0.05] µg·kg−1·min−1 norepinephrine equivalents, P < 0.001). We did not observe an association between the intraoperative use of vasopressin and severe acute kidney injury after liver transplantation (adjusted odds ratio: 1.29; 95% confidence interval: 0.92-1.80). Vasopressin use was not associated with a higher hazard of experiencing graft failure or related outcomes over time (hazard ratio = 1.17, P = 0.44). Conclusions. In patients requiring high doses of intraoperative vasopressors during liver transplantation, vasopressin use was not associated with an increased risk of severe postoperative acute kidney injury or decreased graft survival.